Montaigne, ethics, the modern "way" - Rodríguez Jaramillo, Antonio (Estudios de Filosofía, 2006)
Montaigne composes a modern Ethics defined by the exercise of his Auto-critical Thought which, united with a philosophical method, treats the construction of the self or a philosophical "way of doing things ". The reflections tries to answer, simultaneously, two issues: How can he provide himself of an ethics that enables him To lead an ordered and sensible existence, when the human condition is marked by disorder and extravagance? And: How is it possible for him to found a modem ethics —before Descartes— with a sceptical position?